Communication, Sportsmanship, and Negotiating Ethical Conduct on the Digital Playing Field. (April 2017) - Smith, William Roth
This study examines sportsmanship and ethics on the digital playing field of Strava—a mobile fitness application (app) that records bicycle rides and uploads the data to an online network of other users. Specifically, the study utilizes a social shaping and construction of technology theoretical framework to investigate and discuss how users of Strava communicatively negotiate what it means to be an ethical user of the technology. Drawing on interviews and participant observations of 47 users of the cycling-focused fitness app, the study presents how users perceive and understand online and off-line actions in terms of ethical conduct. Findings indicate that users view actions as indeterminate or disreputable . While disreputable actions are considered outright cheating, indeterminate actions remain in a gray area that is ethically questionable. The study details how the communicative features of Strava allow users to enact sportsmanship through kudos (e.g., congratulatory comments) and refereeing (e.g., flagging user data). This article concludes by offering examples of how relevant social groups are beginning to shape the sports technology.